B chromosome and NORs polymorphism in Callichthys callichthys (Linnaeus, 1758) (Siluriformes: Callichthyidae) from upper Paraná River, Brazil - Konerat,Jocicléia Thums (2014)
B chromosomes are extra chromosomes from the normal chromosomal set, found in different organisms, highlighting their presence on the group of fishes. Callichthys callichthys from the upper Paraná River has a diploid number of 56 chromosomes (26 m-sm + 30 st-a) for both sexes, with the presence of a sporadically acrocentric B chromosome. Moreover, one individual presented a diploid number of 57 chromosomes, with the presence of a morphologically ill-defined acrocentric B chromosome in all analyzed cells. The physical mapping of 5S and 18S rDNA shows multiple 5S rDNA sites and only one pair of chromosomes with 18S sites in C. callichthys, except for two individuals. These two individuals presented a third chromosome bearing NORs (Ag-staining and 18S rDNA) where 5S and 18S rDNA genes are syntenic, differing only in position. The dispersion of the 18S rDNA genes from the main st-achromosome pair 25 to one of the chromosomes from the m-sm pair 4 would have originated two variant individuals, one of which with the ill-defined acrocentric B chromosome. Mechanisms to justify the suggested hypothesis about this B chromosome origin are discussed in the present study.